Seminal analysis, cryogenic preservation, and fertility in matrinxã fish, Brycon cephalus (Günther, 1869) - Ninhaus-Silveira,Alexandre (2006)
Aiming to improve fish reproduction techniques, the characterization and cryopreservation of semen of Brycon cephalus were performed. The seminal characteristics observed were: an almost transparent, milky semen with a mean volume of 4mL, and sperm concentration of 9.617±1.630 x 10(6) spermatozoa/mm³. Spermatozoa (length = 31.288 ±4.47µm) were of the aquasperm type and displayed a small, round head (length = 1.727 ±0.18 µm; width = 1.752 ±0.17µm) without acrosomal vesicle, nucleus with highly condensed chromatin forming coarse clots and centriolar complex located in the nuclear fossa; a midpiece (length = 2.561±0.44µm), narrowed rearward, with a cytoplasmic canal; and a flagellum (length = 29.521 ±4.37µm). Fertilization tests with thawed semen demonstrated a significant effect (alpha= 0.05) on the increase of thawed semen fertility with diluent type B in both 0.5mL and 4.0 mL straws. No significant effect (alpha= 0.05) on hatching rate was observed in both straw sizes used.